A interiorização da Universidade Estadual de Goiás : uma abordagem a partir da oferta dos cursos regulares – 2010 - 2019 - Santos, Luiza Rodrigues dos (2023)
The present study is part of the line of research State and Educational Policies of the Graduate Program in Education at the State University of Goiás (UEG) and has as its theme the internalization of the UEG via the offer of regular courses in the face-to-face modality. The general objective is to interpret and analyze the effectiveness of UEG in the process of internalization of higher education as the only public, secular and free state university in the state of Goiás. It takes as an investigative problem the historical process of UEG in the period 2010-2019 and whether it has contributed to the process of internalization of public higher education in the state of Goiás. The research, with a qualitative approach, is based on historical- dialectical materialism. Bibliographical and documentary in nature, the research used the categories regionalization and interiorization, for a critical and contextualized analysis of the process of expansion and offer of face-to-face courses, and the implications for the institutional policy of the UEG. Among the many selected authors, we mention Chauí (2003), Dardot and Laval (2016), Harvey (2008), Marx and Engels (1977), Saviani (2009, 2010, 2011, 2020), Sguissardi, (2002, 2006, 2008), among other important theorists. With the results of the investigation in hand, the main findings of the research are that the paths followed by this relevant social institution have been influenced by the ongoing movement of commodification of higher education based on neoliberal precepts, that is, the managerial perspective typical of private institutions inserted in the daily life of public services. With regard to the UEG, in line with its institutional mission, the research found that this University has contributed to the society of Goiás by providing public, free and quality higher education for several students in the interior of the state of Goiás, however, little progressed in proposing new courses, since course expansion actions have not been significantly affecting the issue of interiorization, which has remained in the same proportion throughout the historical series analyzed.